Visualization and Bibliometric Analysis of Vocational Education Articles in ASEAN Member States on the Scopus Databases - Abi Hamid, Mustofa; Darmawan, Ilham Akbar; Fadli, Radinal; Mutiara, Indra; Setiawan, Dedi; Hakiki, Muhammad (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: This study aimed to analyze the bibliometric characteristics and trends of Vocational Education articles in ASEAN Member States on the Scopus Databases, including co-ocurrence by keywords, citation, co-citation, and bibliographic coupling.Methods: Data were obtained from the Scopus databases in January 2021. The articles were searched using the keyword “Vocational Education” with limited affiliations from ASEAN member states on the Scopus database. The search was limited in the last decade (2011 - 2020) with the article type. Descriptive statistics used in this study were visualization and bibliometric analysis using VOSviewer version 1.6.14.Results: 642 articles on Vocational Education published in 160 journals, with the Journal of Technical and Education and Training as the most popular. Several keywords often appeared and used in the articles were vocational education, human, male, female, education, learning, student, and teaching. Bibliometric analysis showed that 21 documents had the largest citation, 24 journals had the largest co-citation network, and 185 documents had the largest bibliographic coupling. Conclusions: Research in the Vocational Education field by Southeast Asia authors has increased significantly over the last decade. Researchers are increasingly active and productive in producing scientific work and a stronger collaborative network. The Vocational Education topic is increasingly interesting and relevant to current issues so that it is still very open and has an opportunity for future research according to research trends in the Vocational Education field.